Beyond the duties of a bishop - Pavel Gojdič, Righteous among the Nations - Borza, Peter (Nasza Przeszłość, 2022)
The State of Israel awarded the Greek Catholic Bishop Pavel Gojdič the title of Righteous Among the Nations in 2007. In the critical years 1939-1945, he publicly stood up for the persecuted Jews and saved many from death. The study focuses on the analysis of his personality and attitudes to the Slovak Jewish community. It reveals his way of thinking and the specific examples which show us how it was manifested in relation to the persecuted. The study also contains the attitude of the Slovak elites towards the bishop and his activities in Slovakia.